Ecophysiology of Layered Macroalgal Assemblages: Importance of Subcanopy Species Biodiversity in Buffering Primary Production - Tait, Leigh W.; Schiel, David R. (Frontiers in Marine Science, 2018)
Shallow coastal rocky reefs worldwide have faced large-scale loss of biodiversity, yet little is known about the contributions of highly diverse multi-layered autotrophic species to ecosystem function over long periods. In this study we tested the role of functional diversity on net primary productivity (NPP) of macroalgal assemblages in one-off, and multi-year experiments. We removed canopy (perennial fucoid), mid-canopy and basal algae (turfing and encrusting algae) in intertidal assemblages and used in situ photorespirometry to measure recovery of NPP over 2 years. Experimental removal of the canopy caused a >50% decline in NPP, which remained significantly lower than undisturbed assemblages for up to 24 months. Removal of midcanopy and basal algae reduced NPP by >25%, but converged with controls after just 6-12 months. Canopy loss greatly reduced NPP for long periods and productivity began recovering only after the recruitment of the canopy-forming species. Subcanopy species composition varied with experimental disturbance treatment and through time, but consistently contributed to total assemblage NPP. High irradiance in the shallow intertidal zone may be vital to a maximizing the efficiency of light harvesting, and the spatial and temporal variations in species composition may play a critical role in buffering carbon fixation of macroalgal assemblages.